THE CONSTITUTION AND THE CONSTITUTIONALISM IS THE CONSTITUTION CONDITION SINE QUA NON FOR THE CONSTITUTIONALISM - Hristovska, Jelena Trajkovska (PEOPLE: International Journal of Social Sciences, 2018)
This paper analyses the relation between the constitution and constitutionalism. It elaborates the traditional notion of constitutionality and separate factors determining their reality and compliance with the constellation of real social relations. The paper also elaborates concepts of limited constitution, symbolic constitution and the idea of constitution behind the constitution, given the dilemmas these categories open in relation to the constitutional and judicial control of the constitutionality and which are more and more challenging for the constitutional and legal science. Often the effect of “broken mirror” especially if the aforementioned concepts are used may create a completely distorted image of actual situations. That raises the question: Is constitutional review possible without written Constitution? Is constitution invisible, that is, constitution is what the judges say is a constitution? The paper deals with the question does constitutional judges begin with its reconstruction in the process of interpretation of the “mischievous phrases” of the constitution? Does the taking away of the “traditional” constitution from the constitutional judges really jeopardize the concept of constitutionalism? Finally, it seems that the constitutional legal science rigidly adheres to the traditional notion about the constitution in the formal sense as stable, written and codified act. It can be concluded that the constitution is the core of the constitutionalism. However constitution and constitutionalism cannot be equated. The implementation and fostering of the constitutionalism in practice seems to be conditioned by a number of other factors such as political culture, constitutional history, political, social and legal certainty and economic stability. The constitution may project the idea of achieving constitutionalism, but whether it will be implemented in the real sense of the word depends finally on the state and the will of the society.